2005
DOI: 10.1007/s00247-005-1479-6
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic fibroma of the mandible in an infant

Abstract: We report the CT and MR imaging findings of a case of a desmoplastic fibroma of the mandible in a 6-month-old girl who presented with a rapidly enlarging facial mass and who represents one of the youngest reported children with this rare tumor. Although imaging is non-specific and these lesions are best distinguished histologically, the desmoplastic fibroma should be considered when there is an occurrence of any bubbly or cystic expansile mandibular lesion presenting in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…3 Most patients affected are younger than 30 years, and DF of the jaw has been reported in children as young as 6 months of age. 5 Maxillary DFs present with signs and symptoms similar to those in our case, with a gradually increasing asymptomatic facial swelling. Other reported symptoms include pain at the affected area (15%), tooth mobility (7%), and proptosis (2.5%).…”
Section: Report Of a Casesupporting
confidence: 74%
See 2 more Smart Citations
“…3 Most patients affected are younger than 30 years, and DF of the jaw has been reported in children as young as 6 months of age. 5 Maxillary DFs present with signs and symptoms similar to those in our case, with a gradually increasing asymptomatic facial swelling. Other reported symptoms include pain at the affected area (15%), tooth mobility (7%), and proptosis (2.5%).…”
Section: Report Of a Casesupporting
confidence: 74%
“…Most radiologic differential diagnoses of DF include globulomaxillary cyst, ameloblastoma, odontogenic myxoma, aneurysmal bone cyst, juvenile ossifying fibroma, chondromyxoid fibroma, and sarcoma, including rhabdomyosarcoma. 5 Histologic diagnostic criteria of DF as established by the World Health Organization include low to variable cellularity, ovoid or elongated cells, and uniform nuclei without atypia, pleomorphism, or mitotic activity. 3 These cells are supported by a matrix of collagenized to hyalinized connective tissue and are contained by ill-defined cytoplasmic membranes with cytoplasmic extension that merge with the surrounding stroma.…”
Section: Report Of a Casementioning
confidence: 99%
See 1 more Smart Citation
“…On MRIs, the majority of reported cases are osteolytic with hypointense to isointense signals on both T1 and T2-weighted images and prominent T2 shortening [12]. Wippold et al [13] reported a hypointense lesion on unenhanced T1-weighted images that became greatly enhanced after administration of intravenous contrast medium and was hyperintense on the long TR sequences. Treatment modalities and outcomes were documented in 72 % of the cases (109/152).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical options include enucleation, curettage, and wide local resection. As DF has no true capsule and often invades adjacent tissue, there is a high rate of recurrence for incomplete treatment [14]. A study done by Said-al-Naief in 2006 showed that there was a 0% recurrence with wide local excision, whereas curettage alone led to 70% recurrence followed by 20-40% recurrence with simple enucleation [13].…”
Section: Literature Review and Discussionmentioning
confidence: 99%